2014
DOI: 10.1007/s00709-014-0616-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of heat stress on auxin distribution in transgenic B. napus microspores and microspore-derived embryos

Abstract: Plant embryogenesis is regulated by differential distribution of the plant hormone auxin. However, the cells establishing these gradients during microspore embryogenesis remain to be identified. For the first time, we describe, using the DR5 or DR5rev reporter gene systems, the GFP- and GUS-based auxin biosensors to monitor auxin during Brassica napus androgenesis at cellular resolution in the initial stages. Our study provides evidence that the distribution of auxin changes during embryo development and depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 50 publications
(60 reference statements)
0
30
1
1
Order By: Relevance
“…Another similitude with the ZE pattern was the accumulation of DR-5 activity in the cell that would originate the hypophysis. Later and before the transition to heart stage of the embryo, the DR-5 activity was higher during the establishment of provascular cambium and the cotyledonar leaf primordia, which suggest that Ax distribution gradient is necessary for the correct pattern formation of the development embryo (Dubas et al 2014).…”
Section: Auxin Response During the Somatic Embryogenesismentioning
confidence: 98%
See 1 more Smart Citation
“…Another similitude with the ZE pattern was the accumulation of DR-5 activity in the cell that would originate the hypophysis. Later and before the transition to heart stage of the embryo, the DR-5 activity was higher during the establishment of provascular cambium and the cotyledonar leaf primordia, which suggest that Ax distribution gradient is necessary for the correct pattern formation of the development embryo (Dubas et al 2014).…”
Section: Auxin Response During the Somatic Embryogenesismentioning
confidence: 98%
“…In general, there are low levels of IAA in the suspensor-like structure and higher levels in the proper embryo. Using mild heat temperature treatment to induce the SE in B. napus and GFP as a marker, under control of the synthetic auxin DR5-promoter, Dubas et al (2014) founded that after the induction of SE and the first asymmetric transverse division, the DR-5 activity was detected in both apical and basal cell. However, the basal cell had a higher activity suggesting that the Ax flux was carried out from the basal cell to the apical cell Jenik et al 2007), the same pattern during the first division of ZE.…”
Section: Auxin Response During the Somatic Embryogenesismentioning
confidence: 98%
“…Brassica napus was one of the first plants in which temperature-treatment was used to stimulate the embryogenic program (Lichter 1982). For instance, microspores pretreated at 32°C for 24 h tended to develop a suspensor-like structure as occurs during ZE, whereas a prolonged treatment up to five days prevented the formation of suspensor in the embryos (Dubas et al 2011;Dubas et al 2014). After that, the temperature was decreased 12-15°C day/7-10°C night, until bud collection, and only then, the heat shock treatment was imposed (Belmonte et al 2006;Prem et al 2012;Seguí-Simarro et al 2003).…”
Section: Temperature Stress Treatmentsmentioning
confidence: 99%
“…In Brassica napus, when a MDE with suspensor is formed, the patterning of the embryo requires polar auxin transport, while when in absence of suspensor, the patterning is auxin-independent at first, but triggered by exine rupture accompanied by auxin gradient polarization (Dubas et al 2014;Soriano et al 2014;. Arabinogalactan proteins have also been demonstrated to be involved in early pattern formation and polarity establishment in MDEs .…”
Section: Tissue Patterning and Embryo Developmentmentioning
confidence: 99%
“…It has been demonstrated that, in this route, cell polarity in embryogenic microspores is induced and controlled by early dehiscence of the exine wall , accompanied by intracellular auxin polarity (Dubas et al 2014;Soriano et al 2014).…”
Section: Role Of Stress In Embryogenic Inductionmentioning
confidence: 99%